The impact of Artificial Light at Night (ALAN) on biodiversity: flora and fauna at Kebun Raya Bogor - Fauzia, Assyifa (Institute of Advance Science, Social, and Sustainable Future, 2024)
Background: Artificial light at night (ALAN) poses significant ecological challenges by altering the natural light environment. Plants and animals have evolved to depend on natural light cycles for their physiological and behavioral processes. This study investigates the impact of ALAN on the biodiversity of flora and fauna at Kebun Raya Bogor (KRB), a key site for understanding these effects. Methods: This research employs a literature review approach to analyze the effects of ALAN on flora and fauna. By examining existing studies and data, the review focuses on changes in plant physiology, including photosynthesis and growth patterns, as well as alterations in animal behavior, such as foraging, mating, and migration. The review synthesizes findings from various sources to assess the impact of ALAN on biodiversity at KRB. Results: Findings indicate that ALAN disrupts plant photosynthesis and growth, particularly affecting deciduous trees and altering reproductive and growth patterns. For fauna, ALAN significantly impacts the behavior of nocturnal species such as bats and birds, affecting their feeding, mating, and migratory patterns. The disruption in natural light cycles due to ALAN leads to ecological imbalances and may compromise the biodiversity of KRB.